Digital natives and deferred payments: A qualitative study of young consumers' e-commerce BNPL behaviors - Fitrisam, Syarifah Aliyah; Iradat, Muhammad Isra; Iskandar, Rizkiani; Utami, Ayu Putri; Rhamadhani, Rika Febby (Privietlab, 2025)
The swift adoption of Buy Now, Pay Later (BNPL) options has significantly changed the online shopping experience, particularly among younger demographics, such as Generation Z and Millennials, in Indonesia. Given that many individuals in this age group do not possess traditional credit cards, BNPL has become a favored and easily accessible solution that fits their digital lifestyle. This research examines how the rise of BNPL affects the purchasing choices, financial outlooks, and expressions of identity of younger consumers. The results indicate a transition in consumer behavior that prioritizes convenience, facilitated by digital platforms, where payment methods serve as a form of self-expression and reflect personal lifestyle preferences. The findings highlight the social and psychological aspects of deferred payment systems, offering valuable insights into the evolving dynamics between young consumers and financial innovation.